Light-activated electrochemistry without surface-bound redox species - Kashi, M.; Silva, S.; Yang, Y.; Gonçales, V.; Parker, S.; Barfidokht, A.; Ciampi, Simone; Gooding, J. (Pergamon, 2017)
© 2017 Elsevier Ltd Semiconducting electrodes that are in depletion, can support appreciable electron transfer only when illuminated. This phenomenon has been implemented on silicon electrodes passivated by a protective organic self-assembled monolayer (SAM) to confine electrochemistry to microscale regions on an unstructured electrode surface by shining light only on those regions. This method, referred to as light-activated electrochemistry (LAE), has so far only been studied using electrodes with surface-bound redox mediators that are either covalently or electrostatically attached to a SAM-modified silicon electrode. In the current report, we extend LAE to redox species in solution using gold nanoparticles (AuNPs) attached to the SAM-modified silicon electrodes. Cyclic voltammetry showed that faradaic electron transfer to redox species in solution can be switched on/off using light. Furthermore, the modified silicon electrodes were stable to more than 650 redox cycles, even when scanning to anodic potentials, with negligible oxide growth and no noticeable change in the voltammograms. Using a variety of redox species in solution, it was shown that with n - -Si-SAM-AuNP electrodes negligible current was observed in the dark but appreciable faradaic electrochemistry was observed upon illumination. It was also shown that to ensure electron transfer proceeded via the AuNPs only, nonspecific adsorption of the redox species to the monolayer surface needed to be avoided.